Pengaruh Kemampuan Pemecahan Masalah Matematik dan Motivasi Belajar terhadap Numerasi Siswa Kelas 4 SD - Jusniani, Nia; Nursofa, Wina; Fauziyanti Rahmi, Dini (LPPM Universitas Terbuka, 2023)
Numeration has an important role in the future of students. Train students' basic numeracy skills from an early age to prepare the next generation. The motivational boost factor in learning is one of the things that needs to be raised in learning efforts at school. The type of research used is quantitative research. The population of this study was 33 grade 4 students at SDN Sindanglaka Cianjur Regency. The student motivation questionnaire instrument for learning motivation is 25 statements, while problem-solving or problem-solving uses 2 questions. The dependent variable is numeracy ability in grade 4 elementary school, with the form of a test instrument as many as 2 questions. The results of the study concluded that there was no influence of mathematical problem-solving ability and learning motivation on numeracy in grade 4 students at SDN Sindanglaka. Because the application of numeracy in schools has just been implemented in the independent curriculum students do not understand numeracy.